Using Four Reading Methods (FRM) in Teaching Intensive Reading Class (IRC) to Enhance Students’ Reading Skill - Bobby Octavia Yuskar; Marsandi Manar; Suhono Suhono (CV. Creative Tugu Pena, 2023)
This research focuses on teaching Intensive Reading (IR) using Four Reading Methods (FRM) to students of English Department. The subject of this research are twenty students divided into two groups, ten male and ten female participants. Each student had to read certain texts intensively and delivered a presentation explaining the information obtained from the text in limited time. The method used in this research is qualitative research that paid attention to the utilization of Four Reading Methods (FRM) as one of teaching techniques utilized by the researcher in teaching Intensive Reading Class (IRC) to students English Department. Each method was interconnected to each other as unity that helped students in presentingtheir learning outcomes obtained from particular reading passage they had already read intensively. The scoring was obtained according to the score from each method. This teaching technique was compiled by the researcher from a number of reliable resources. The Four Reading Methods (FRM) as a solution to enhance the reading skills of the students and to improve their presentation skills when they deliver their learning outcomes in the form of presented materials. There were numerous theories utilized by the present study in order to have solid scientific background. The theories were taken from several scholars who already conducted researchers in teaching intensive reading in class. The aim of this research is to provide a solution to fellow lecturers in providing flexible methods as an alternative in teaching Intensive Reading (IR) to their students. In addition, three previous studies in teaching reading were incorporated as significant contribution to enrich the quality of this research. Keywords: Four Reading Method, Intensive Reading Class, Reading Skill